A Survey for Various Techniques of Image Enhancement - Singh, Abinasi; Singh, Rachhpal (International Journal of Computer Sciences and Engineering, 2020)
Image Enhancement is one of the important and tough techniques in digital image processing. The main objective of image enhancement is to find out the hidden details in an image. Image Enhancement improves the quality of image for human presentation. Contrast increment, elimination of noise and blurring and enlightenment of details are examples of enhancement operation. Image enhancement is basically divided into two main categories such as spatial domain and Frequency domain. In this paper we discuss and compare these two techniques with their related techniques. Thus, the contribution of this paper is to various image enhancement technique.